Analysis of the Effect of Health Service Quality on Patient Satisfaction in Internal Medicine Inpatient Room of Hospital Level II Military Area Health Medan - Shelly Shelly; Asyiah Simanjorang; Yuniati Yuniati (Newinera Publisher, 2021)
The purpose of this study was to determine the effect of quality on patient satisfaction in the hospital room for the Level II Military area health Medan in 2020. The research design used in this study was an analytic survey with a cross sectional design. The population in this study were all patients in the Internal Medicine Room of hospital Level II Military area health Medan as many as 167 people. The number of samples that will be studied is 118 people. Data analysis was performed using univariate, bivariate and multivariate analyzes. The statistical test used was the chi square test and logistic regression.The results of the chi square test showed that the technical competence variable obtained p-value = 0,000, efficiency p-value = 0,000, and patient safety p-value = 0,000 < α 0.05, meaning that there was an influence between technical competence, efficiency and Patient safety on patient satisfaction, from the results of the multivariate analysis, it was found that the most influential variable in this study was the patient safety variable. The conclusion is that there is an influence between technical competence, efficiency and patient safety, while multivariate analysis shows that the most dominant factor is the variable of patient safety on family satisfaction. It is recommended that the hospital be able to improve the technical competence of nurses in the inpatient room of the Public Health Service in Medan by holding training and workshops both internal and external training.